Pengembangan E-Modul Berbasis Kearifan Lokal dan Kecakapan Hidup - Adi Tri Atmaja; Nurul Murtadho; Sa’dun Akbar (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: The purpose of research and development is to produce an electronic module based on local wisdom and life skills. The product is developed according to the stages of the ADDIE model. The feasibility of the e-module is known from the results of expert validation, and an assessment of the attractiveness, practicality, and effectiveness of the product from users. The average validation results of material experts reached 89.5%, design experts 87%. Then the field trial by the teacher obtained an average of 93% attractiveness, 93% practicality, and by students it reached 91% attractiveness percentage, 90% practicality and 96% class completeness effectiveness. The results of research and product development can be categorized as suitable for use in learning.Abstrak: Tujuan dari penelitian dan pengembangan adalah memproduksi modul elektronik berbasis kearifan lokal dan kecakapan hidup. Produk dikembangkan sesuai tahapan model ADDIE. Kelayakan e-modul  diketahui dari hasil validasi ahli ahli, dan penilaian kemenarikan, kepraktisan dan keefektifan produk dari pengguna. Rata-rata hasil validasi ahli materi mencapai 89.5%, ahli desain 87%. Kemudian uji coba lapangan oleh guru diperoleh rata-rata hasil kemenarikan 93%, kepraktisan 93%, dan oleh peserta didik mencapai persentase kemenarikan 91%, kepraktisan 90% dan efektivitas ketuntasan kelas 96%. Hasil penelitian dan pengembangan produk dapat dikategorikan layak digunakan pada pembelajaran.